TINJAUAN EFEKTIFITAS HUKUM UNDANG-UNDANG PERLINDUNGAN DATA PRIBADI DALAM KASUS KEBOCORAN DATA DI INDONESIA - Rizqy Dimas Monica; Exanti Tira Permatasari (Institut Agama Islam Negeri Fattahul Muluk Papua, 2025)
This study aims to analyze the effectiveness of the implementation of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) in addressing and preventing cases of data breaches in Indonesia. This research employs a normative juridical method using statutory and conceptual approaches through the examination of laws and regulations, academic literature, scientific journals, and previous studies relevant to personal data protection. The findings indicate that although the PDP Law has adopted various data protection principles aligned with the European Union’s General Data Protection Regulation (GDPR), its implementation effectiveness in Indonesia still faces several challenges. These obstacles include suboptimal law enforcement mechanisms, the absence of a fully functional and independent supervisory authority, and the low level of compliance among public and private sectors with personal data protection obligations. In addition, limitations in cybersecurity infrastructure and low levels of digital literacy and public awareness also affect the effectiveness of the implementation of the PDP Law. Therefore, strengthening implementing regulations, enhancing institutional capacity, and harmonizing data protection standards are necessary to ensure effective protection of citizens’ privacy rights.